Технология женской и детской легкой одежды - Труханова Антонина Тимофеевна (Лег. и пищ. пром-сть, 1983)
Экземпляры: (20200123) / Инвентарный номер: 5368 / Сис.шифр: 6П9.33(075.1) / Авт.знак: Т 80 / ГРНТИ: 64 / ББК: 6П9.33(075.1)